Shade tree cover criteria for non-point source pollution control in the Rainforest Alliance coffee certification program: A snapshot assessment of Costa Rica's Tarrazú coffee region. (July 2016) - de Jesús-Crespo, R.; Newsom, D.; King, E.G.; Pringle, C.
Highlights: 40% tree cover in agroforestry reduces sediment exports to streams. This trend is best detected during the transition from dry to rainy season. Our findings support a current sustainability certification guideline. This guideline is effective if implemented at the sub-watershed scale. Shade tree cover criteria alone have limited impact on agrochemical reduction. Abstract: Management of non-point source pollution is of great importance in the context of coffee agriculture, as this land use often coincides with headwater streams that influence water quality at the basin scale. Sustainability certification programs, such as the Rainforest Alliance (RA), provide management guidelines that promote non-point source pollution control in coffee. One of these practices is the maintenance of shade trees within farms, required by RA at a minimum of 40% shade tree cover. Here we assess the effectiveness of this practice in Tarrazú, a high elevation coffee growing region in Costa Rica. We monitored indicators of non-point source pollution in streams with both high and low shade tree cover. Streams with High Shade Tree Cover (HSTC, N  = 5 subwatersheds) had 35–55% cover, approximating or exceeding the RA recommendation of at least 40%; and streams with Low Shade Tree Cover (LSTC, N  = 5 subwatersheds), had 18–31% cover. We monitored the ten study streams during the dry (April & December), transition (July), and peak (October) rainfall seasons of 2013, and compared responses using t -tests. We found support for the effectiveness of shade tree cover in controlling non-point source pollution: HSTC streams had significantly ( p  = 0.042) lower mean annual turbidity and significantly ( p  = 0.004) lower turbidity during the transition season. HSTC streams also had significantly ( p  = 0.05) lower conductivity values during the transition period, although this trend was weaker through the year. Subwatersheds with HSTC streams were characterized by a higher percentage of RA-certified coffee than LSTC streams. Our study provides evidence of the benefits of RA shade tree cover criteria for managing water quality within high elevation tropical agro-ecosystems, especially if implemented at the watershed scale. These results contribute to our understanding of the role of agroforestry certification on tropical ecosystem conservation, and are the first account of the effectiveness of a specific coffee certification guideline on non-point source pollution control.